Revir. (Stockholm : Kulturhuset Stockholm, 1994)
Bhimji, Zarina ; Edefalk, Cicilia & Westphalen, Olav ; Engström, JH ; Gmelin, Felix ; Hagdahl, Peter ; von Hausswolff, Annika ; Hietala, Jan ; Kabakov, Ilya ; Lindberg De Geer, Marianne ; Lövin, Björn ; Nordenskiöld, Anna ; Rodriguez, Joseph ; Rollof, Ulf ; Sidén, Ann-Sofi ; Sjöberg, Ingvar ; Widoff, Anders ; Wodiczko, Krzysztof
Revir / Territory, Kulturhuset, Stockholm, 23 september 1994 - 8 januari 1995
kunstcatalogus